Relationship Between Arm Muscle Strength and Concentration on Archery Accuracy in VIJAS Archery Club Athletes - Sulistiyowati, Oktavia Suci; Muhammad, Muhammad; Yudhistira, Dewangga; Siena Ar Rasyid, Muhammad Labib; Ashadi, Kunjung (LPPM Universitas Jambi, 2026)
Archery requires good physical and mental abilities in order for athletes to produce accurate shots. This study aimed to determine the relationship between arm muscle strength and concentration on archery accuracy in Vijas Archery Club athletes. This study employed a quantitative method with a multiple correlational approach. The research sample consisted of 20 Vijas Archery Club athletes selected using a purposive sampling technique. Data were collected through an arm muscle strength test using an Expanding Dynamometer, a concentration test using the Grid Concentration Test, and a shooting accuracy test at a distance of 30 meters. The data were analyzed using the Pearson correlation test and multiple linear regression. Result: The results showed that there was a positive and significant relationship between concentration and shooting accuracy, with a correlation value of 0.616 and a significance value of 0.004. In addition, there was a very strong relationship between arm muscle strength and shooting accuracy, with a correlation value of 0.927 and a significance value of 0.000. The results of multiple linear regression indicated that arm muscle strength had the most dominant influence on shooting accuracy compared to concentration. Based on the results of the study, it can be concluded that arm muscle strength and concentration are related to archery accuracy. However, arm muscle strength is the most influential factor in improving the shooting performance of archery athletes